IL-36α Promoted Wound Induced Hair Follicle Neogenesis via Hair Follicle Stem/Progenitor Cell Proliferation - Gong, Lin; Xiao, Jian; Li, Xiaokun; Li, Yuanhong; Gao, Xinghua; Xu, Xuegang (Frontiers in Cell and Developmental Biology, 2020)
Background: Wound-induced hair follicle neogenesis (WIHN) is a phenomenon of hair neogenesis that occurs at the center of a scar when the wound area is sufficiently large. Neogenic hair follicles are separated from the preexisting follicles at the wound edge by a hairless circular region. This WIHN study provides a unique model for developing treatments for hair loss and deciphering the mechanisms underlying organogenesis in adult mammals. Methods: The skin of the mice was wounded by excising a 1.5 × 1.5 cm2 square of full-thickness dorsal skin. iTRAQ technology was used to screen proteins differentially expressed between the inner and outer scar areas in a mouse model of WIHN on post-wounding day 15 to identify the regulators of WIHN. Owing to the overexpression of interleukin-36α (IL-36α) in the de novo hair follicle growth area, the regulating effect of IL-36α overexpression in WIHN was investigated. Hair follicle stem/progenitor cells were counted by flow cytometry while the expression of hair follicle stem/progenitor cell markers (Lgr5, Lgr6, Lrig1, K15, and CD34) and that of Wnt/β-catenin and IL-6/STAT3 pathway intermediaries was detected by qPCR and western blotting. Results: We found that wounding induced IL-36α expression. Incorporation of recombinant murine IL-36α (mrIL-36α) into murine skin wounds resulted in a greater number of regenerated hair follicles (p <0.005) and a faster healing rate. The expression of hair follicle stem/progenitor cell markers was upregulated in the mrIL-36α-injected site (p <0.05). Additionally, mrIL-36α upregulated the IL-6/STAT3 pathway intermediaries. Conclusion: IL-36α is upregulated in de novo hair follicle growth areas, and can promote wound epithelialization and WIHN.